2016
DOI: 10.3126/ajms.v7i6.15197
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry based prediction of dominant hand grip strength in Indian office going females

Abstract: Background: Physical strength can be measured by means of hand grip strength. It is of great use as a functional index of nutritional status. Aims and Objectives: Association of hand grip strength with other variables is studied in order to predict the strength outcomes and to study the effect of factors that can influence hand grip strength performance. Materials and Methods: In the present study the correlations of dominant hand grip strength and anthropometric and body composition variables namely, height, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…But, the correlation of the dominant handgrip strength with the length of the hand and hand span were positive individually but non-significant. Similarly Rawat et al (2016) found a significant correlation was between the handgrip strength and the hand breadth rather than the hand length of 375 Indian office going females. The finding of the present research also consistent with several researches (Vivekanand et al, 2016;Sandhu et al, 2017).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…But, the correlation of the dominant handgrip strength with the length of the hand and hand span were positive individually but non-significant. Similarly Rawat et al (2016) found a significant correlation was between the handgrip strength and the hand breadth rather than the hand length of 375 Indian office going females. The finding of the present research also consistent with several researches (Vivekanand et al, 2016;Sandhu et al, 2017).…”
Section: Resultsmentioning
confidence: 90%
“…After repeated workload the muscle mass is increased, which lead to increase handgrip strength. Thus, a muscle with a large crosssectional area is able to produce maximal force during working (Rawat et al, 2016). A large hand span provides a large surface area during grasping an object in a grip associated work.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, handgrip strength was significantly correlated to height and weight at all anatomical positions and to hand length except position 6 among young adults. Many studies have shown a correlation between height and handgrip strength among different ages [12,21,27,29]. Angest et al have studied the predictive power of demographic measurements on grip and pinch strength.…”
Section: Bmi Discussionmentioning
confidence: 99%
“…While, there was a correlation between handgrip strength and height, weight, BMI, total arm length, and upper arm circumference in the female group [17]. Also, many studies have investigated the predictor value from anthropometric variables for handgrip strength [21,22]. It has been shown that the most predictive value of handgrip strength was height followed by forearm girths [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation